Hubbard model: Pinning of occupation numbers and role of symmetries - Schilling, C (American Physical Society, 2015)
Fermionic natural occupation numbers do not only obey Pauli's exclusion principle, but are even further restricted by so-called generalized Pauli constraints. Such restrictions are particularly relevant whenever they are saturated by given natural occupation numbers λ - =(λi). For few-site Hubbard models we explore the occurrence of this pinning effect. By varying the on-site interaction U for the fermions we find sharp transitions from pinning of λ - to the boundary of the allowed region to nonpinning. We analyze the origin of this phenomenon which turns out be either a crossing of natural occupation numbers λi(U),λi+1(U) or a crossing of N-particle energies. Furthermore, we emphasize the relevance of symmetries for the occurrence of pinning. Based on recent progress in the field of ultracold atoms our findings suggest an experimental setup for the realization of the pinning effect.